Regional LCA in a global perspective. A basis for spatially differentiated environmental life cycle assessment. - Sleeswijk, Anneke Wegener (The International Journal of Life Cycle Assessment)
Background, aim and scope In the context of environmental life cycle assessment (LCA), life cycle impact assessment (LCIA) is one of the central issues with respect to modelling and methodological data collection. The thesis described in this paper focuses on the assessment of toxicity related impacts, and on the collection of normalisation data. A view on the complementary roles of LCA toxicity assessment on the one hand and human and environmental risk assessment (HERA) on the other is presented, and the global, spatially differentiated LCA toxicity assessment model GLOBOX for the assessment of organics and metals is described. Normalisation factors for the year 2000 are calculated on a global as well as on a European level. Goal Adding to the reliability and accuracy of LCIA takes a central place. A global coverage, spatial differentiation, and a distinction between potential and actual impacts are considered as important aspects in this context. Structure The thesis consists of seven chapters. The chapters 1 and 7 are a general introduction and discussion, respectively. The chapteres 2 and 3 form a theoretical basis, focussing on the relationship between LCA toxicity assessment and HERA, and their respective roles in environmental protection. In chapter 4 and 5, the newly developed software model GLOBOX is described, along with conclusions, drawn from an analysis of the results of the model for the substance nitrobenzene. Chapter 6 describes a practical update of LCA normalisation for all LCA impact categories. Conclusion LCA toxicity assessment and HERA are distinct tools with different goals and outputs, but with an overlap with respect to environmental fate and human intake calculation. Although they cannot be merged, it is proposed to combine them in a common software model, which would offer harmonised results with respect to both types of outputs. Existing multimedia fate and exposure models form a useful basis, but to be applicable in LCA, they should combine global coverage with spatial differentiation and they should allow for the assessment of metal emissions. The GLOBOX model offers this combination of features. At the level of separate countries and seas, spatial differentiation of environmental and human exposure characteristics turns out to show large differences between regions with respect to the toxic impacts, calculated to result from a certain emisison of the test substance nitrobenzene. Finally, the GLOBOX model demonstrates that it is possible not only in HERA, but also in LCIA, to assess actual environmental impacts, along with the potential impacts on which LCA traditionally focuses.